2012
DOI: 10.1016/j.jfma.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

A highly specific ELISA for diagnosis of 2009 influenza A (H1N1) virus infections

Abstract: The ELISA is an easy to perform, highly specific, and fairly sensitive diagnostic tool for the 2009 pandemic influenza A (H1N1) virus infections. A strong correlation was found between viral load and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…New tests or techniques for specific microorganisms may help us find the etiology of KD. 48,49 In conclusion, we found that common respiratory viruses, such as enteroviruses, adenoviruses, rhinoviruses, and coronaviruses, were associated with KD. Heterogeneous infectious etiologies may be responsible for KD in different countries as well as during different seasons.…”
Section: Discussionmentioning
confidence: 65%
“…New tests or techniques for specific microorganisms may help us find the etiology of KD. 48,49 In conclusion, we found that common respiratory viruses, such as enteroviruses, adenoviruses, rhinoviruses, and coronaviruses, were associated with KD. Heterogeneous infectious etiologies may be responsible for KD in different countries as well as during different seasons.…”
Section: Discussionmentioning
confidence: 65%
“…ELISA sensitivity decreases after 10 5 (log 10/ml) viral load but QuickVue Influenza A+B test sensitivity decreases after 10 7 (log 10/ml) viral load [51]. In a different study, 1086 sera were analysed from 43 swine herds for different reference strains (H1N1, H3N2, H1N2, H1N1pdm) using ELISA with HI test and it was found that ELISA sensitivity and specificity were higher than HI that were 72.65% and 63.01%, respectively, for the detection of these strains [52,53]. According to these studies, ELISA cannot detect infection at an early stage.…”
Section: Enzyme Linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Rapid techniques for detecting the influenza virus include immunofluorescence and immunoenzymatic assays [ [66] , [67] , [68] ]. For both viruses, real-time RT-PCR represents the gold standard technique [ 69 ]. Rapid immunochromatographic tests will be extremely important for mass screening of individuals in the COVID-19 pandemic [ 70 , 71 ].…”
Section: A Brief Comparison Between Clinical Aspects and Laboratory Dmentioning
confidence: 99%